Primary hyperparathyroidism and concurrent hyperthyroidism in a cat - Kaplan, Eliot (Canadian Veterinary Medical Association, 2002)
A cat was presented for anorexia and vomiting.Hyperthyroidism and primary hyperparathyroidism were diagnosed. A thyroid adenoma and parathyroid adenoma, respectively, were responsible for these conditions. Unilateral thyroidectomy and parathyroidectomy successfully resolved both disorders.